Biochemical and molecular characterization of Pectobacterium carotovorum, the causal agent of soft rot in Peninsular Malaysia - Nazerian, Eisa (2012)
Surveys were conducted between the years 2008 and 2009 in the northern,central and southern regions of Malaysia. The sampling sites included vegetable farms and ornamental greenhouses. A total of 147 samples of chlorotic or necrotic leaves, stems, or fruits with light brown to yellow discoloration and extensive water soaked lesions suspected to be infected by soft rot bacteria of the genus Pectobacterium were obtained from 35 sites. Characteristics of 63 bacterial isolates obtained from these samples were studied based on phenotypic observations and molecular methods. All isolates obtained from diseased samples were identified as P. carotovorum subsp. carotovorum based on phenotypic and molecular features. Biochemical properties clearly showed that P. carotovorum subsp. carotovorum was the main bacterial pathogen affecting vegetables and ornamental plants in Malaysia. The species represented 92% of the total isolates sampled. Twenty one bacterial suspensions at the concentration of 106 CFU/ml derived from the different host plants when inoculated to potato tuber slices,showed clear differences in aggressiveness. The representative isolates elicited HR in tobacco, and produced pectinase caused soft rot symptoms upon inoculation of this bacterial suspension concentration on vegetable and ornamental leaves, roots or stems via pathogenicity tests. The results revealed that all P. carotovorum subsp. carotovorumsequences studied here had similarities between 94-100% with gene bank databases using different primers and these were in agreement with the classification based on physiological and biochemical features, and indicated that P.carotovorum subsp. carotovorum was detected from all the infected plant tissues. Moreover based on PCR amplification of the pectate lyase-encodinggene (pel) and universal rice primer, 16s rRNA analysis, analysis of the intergenic transcribed spacer region (16S-23S rRNA), and ITS-restriction fragment length polymorphism (ITS-RFLP), all isolates were identified as P. carotovorum subsp. carotovorum. In spite of the low number of isolates examined, it was shown that BOXPCR and ERIC-PCR were suitable for characterisation of P. carotovorum subsp. carotovorum. Some similarities and differences were indicated by the pattern of DNA fingerprint in BOX-PCR and ERIC-PCR methods during classification of isolates. In both methods, isolates were placed in three main groups. There was no perfect agreement between the ERIC-PCR and BOX-PCR methods in differentiation of isolates. Even isolates that presented similar patterns in BOX-PCR exhibited different patterns in ERICPCR.